Ischaemia / reperfusion injury in renal transplantation - Koo, D; Dicken D. H. Koo (1999)
﻿ Kidney transplants from both living-related (LRD) and living unrelated (LURD) donors have superior function and survival than transplants from cadaver donors. This may be unsurprising as kidneys from living donors are procured under optimal conditions, from healthy donors with minimal ischaemia times. In contrast, cadaver kidneys are obtained from traumatised donors and may experience extended periods of cold ischaemic storage before transplantation. An immunohistochemical analysis has been performed on biopsies obtained before, and immediately after transplantation, to investigate the potential causes of early inflammatory events associated with cadaver renal transplantation that may influence subsequent graft outcome. An immunohistochemical analysis of biopsies obtained before transplantation demonstrated upregulated expression of endothelial E-selectin and proximal tubular expression of ICAM-1, VCAM-1 and HLA Class II antigens in cadaver donor kidneys. Analysis of donor parameters demonstrated that traumatic physiological events experienced in intensive care around the time of brain death were significantly associated with the induction of proinflammatory antigens. Antigen induction in cadaver donor kidneys before transplantation was significantly associated with early acute rejection. Furthermore, in cadaveric kidneys with long cold ischaemia times, glomerular neutrophil infiltration and deposition of activated platelets expressing P-selectin on intertubular capillaries were detected following reperfusion, in association with impaired short and long term graft function. Expression of inflammatory mediators were absent in all LRD renal allografts before and after reperfusion. A clinical trial was performed to determine whether ischaemia/reperfusion injury may be ameliorated by reflushing cadaver kidneys after cold storage to remove harmful products that may have accumulated in the vessel lumen. Reflushing did not prevent the inflammatory events observed after reperfusion or improve graft function. Therefore, a novel, oxygen free radical scavenger (lec-SOD) was obtained to assess its potential efficacy in preventing ischaemia/reperfusion injury. Lec-SOD bound with high affinity to macro- and microvascular endothelial cells under cold hypoxic conditions following incorporation into Marshall's preservation solution, significantly inhibiting cold hypoxia induced cell death, adhesion molecule induction and neutrophil adhesion. Furthermore, preservation of kidneys with lec- SOD for 18 hr in an experimental model of chronic renal allograft rejection, significantly attenuated neutrophil infiltration and MHC Class I induction day 1 post-transplant, with improved long term renal function. The results presented in this Thesis demonstrate that donor factors and cold ischaemia/ reperfusion injury elicit an early inflammatory response that may influence graft outcome of cadaver kidneys. Refinements in donor management and organ preservation may limit the deleterious effects of ischaemia/reperfusion injury in cadaver renal allografts, increasing graft survival to that observed in living donor transplantation.